Diagnosis and Treatment of Epilepsy using Nanotechnology, Artificial Intelligence and Internet of Things (IoT) - Effrosyni Maria, Kosti; Demetzos, Costas (Pharmakeftiki, 2023)
Over 60 million people worldwide suffer from epilepsy. Despite the high prevalence of the disease, a clinical problem is emerging: The development of resistance to drug therapy. Drug delivery nanosystems, Artificial Intelligence (AI) and the Internet of Things (IoT) appear promising both at the diagnostic and therapeutic levels. This announcement is a review of clinical studies published in authoritative databases. These studies examine the application of drug delivery nanosystems in clinical therapy and diagnosis. At the same time, Artificial Intelligence (AI) and the Internet of Things (IoT) seem to give significant advantages to the treating physician. The application of Artificial Intelligence (AI), the use of Big Data through IoT-based networks, and the utilization of “smart” nanodevices can assist in clinical diagnosis and treatment. Also, drug delivery nanosystems improve biostability, reduce toxicity and control the release of the entrapped drug with better pharmacological effects. A typical example of diagnostic optimization is iron oxide nanoparticles as contrast agents in Magnetic Resonance Imaging (MRI). In addition, in the future, it is sought to design nanosensors that record an epileptic seizure, but have the ability to predict it by informing the patient from his mobile phone.